Electrical and Mechanical Properties of LDPE/PANI Composites - Alkan, Umit; Kilic, Mehmet; Karabul, Yasar; Yamak, Hale Berber; Okutan, Mustafa; Icelli, Orhan (AMER SCIENTIFIC PUBLISHERS, 2016)
The thermal, mechanical and dielectric properties of Low Density Polyethylene/Polyaniline (LDPE/PANI) composites filled were investigated. LDPE/PANI composites were prepared using different weight percentage of PANI by compression molded in an electrically heated press. An objective of this study was to investigate dielectric and mechanical proprieties of LDPE/PANI composite films. The samples were characterized by Fourier-transform infrared spectroscopy analysis (FT-IR), tensile tests, thermogravimetry/differential thermogravimetry (TG/DTA) analysis and dielectric measurements. The FT-IR spectrum showed that PANI remained doped in the composite, and this improved the dielectric and mechanical proprieties of LDPE/PANI composite films. As compared to the mechanical and dielectric properties of pure LDPE, LDPE/0.7 wt% PANI composites have been found to have better mechanical and dielectric properties. The real (epsilon') and the imaginary parts (epsilon '') of the complex dielectric constant were measured in the frequency range of 100 Hz-10(6) Hz at room temperature (RT).
Keywords: LDPE; PANI; Composites; Mechanical Properties; Dielectric Properties; ACID-DOPED POLYANILINE; POLYETHYLENE/POLYANILINE BLENDS; TEMPERATURE; DEGRADATION; NANOFIBERS; POLYMERS; FILMS; TIME; Engineering; Science & Technology - Other Topics; Physics